Blockchain-based security attack resilience schemes for autonomous vehicles in industry 4.0: A systematic review. (September 2020) - Gupta, Rajesh; Tanwar, Sudeep; Kumar, Neeraj; Tyagi, Sudhanshu
Abstract: Vehicles automation is one of the applications of smart transport system (STS), and has already been used by many automotive industries, such as Uber, Google, and Toshiba, on trial basis across the globe. These trials have faced many safety, privacy, and security issues, such as impersonation, Denial-of-Service (DoS), timing, and wormhole attacks, which raises many questions and concerns over the usage of these, keeping in view of the safety of the passengers. Although there exists many solutions in the literature for the above issues, but most of these are based upon the centralized architecture having a single point of failure. Motivated from the aforementioned discussion, in this paper, we analyze and discussed the threat classification pertaining to autonomous vehicles (AV) by using the authentication, accountability, and service availability. We highlighted the countermeasures for AV cyberattacks along with their implementation issues and explore how blockchain can overcome these issues. Also, a blockchain-based integrated AV architecture is discussed to mitigate the security and privacy issues with service availability. Finally, we explore the open issues and challenges of blockchain-based AV system.